1997
DOI: 10.1523/jneurosci.17-16-06142.1997
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neuronal Endocytosis and Protease Delivery to Early Endosomes in Sporadic Alzheimer’s Disease: Neuropathologic Evidence for a Mechanism of Increased β-Amyloidogenesis

Abstract: The early endosome is the first vacuolar compartment along the endocytic pathway. It is the site of internalization and initial processing of amyloid precursor protein (APP) and apolipoprotein E (ApoE), two proteins of etiological importance in Alzheimer's disease, and a putative site of ␤-amyloid peptide (A␤) formation. Here, we identify early endosomes in human pyramidal neurons, using specific compartmental markers and morphometry, and show that in Alzheimer's disease individual endosomes display up to 32-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
306
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(340 citation statements)
references
References 68 publications
28
306
2
4
Order By: Relevance
“…Another variable to consider is changes in redoxosome size; our estimates for the flux of O 2 -are based on a diameter of 200 nm (Table 1). This estimate is consistent with the literature for early endosomes (7,8,28,43) and with our own studies evaluating redoxosomes by EM (42). However, endosome size is very dynamic and changes rapidly as endosomes traffic and fuse with other compartments.…”
Section: Lane 5 Vs 8) No Il-1r1=supporting
confidence: 92%
“…Another variable to consider is changes in redoxosome size; our estimates for the flux of O 2 -are based on a diameter of 200 nm (Table 1). This estimate is consistent with the literature for early endosomes (7,8,28,43) and with our own studies evaluating redoxosomes by EM (42). However, endosome size is very dynamic and changes rapidly as endosomes traffic and fuse with other compartments.…”
Section: Lane 5 Vs 8) No Il-1r1=supporting
confidence: 92%
“…A␤ aggregates also destabilize the lysosomal membrane (39), which further compromises lysosomal function and induces leakage of hydrolases into cytoplasmic compartment, contributing to ultimate neuronal death (40,41). Several studies have shown that endosome/lysosome abnormality, including their enlargement, is often induced in early stages of AD (18,19,42,43). Furthermore, presenilin 1 (PSEN1) mutations, causing early-onset AD, induce a disturbed lysosomal/autophagy phenotype by affecting lysosome acidification and proteolysis (44).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include modulation of the deposition and clearance of amyloid ␤ (A␤) peptides and the formation of plaques (9 -15), modulation of A␤-caused synaptic and cholinergic deficits (16), acceleration of age-and excitotoxicity-related neurodegeneration (17), impairment of the antioxidative defense system and mitochondrial function (18 -21), dysregulation of neuronal signaling pathways (22), altered phosphorylation of tau and neurofibrillary tangle formation (23)(24)(25)(26)(27)(28), depletion of cytosolic androgen receptor levels in the brain (29,30), potentiation of A␤-induced lysosomal leakage and apoptosis in neuronal cells (31), and promotion of endosomal abnormalities linked to A␤ overproduction (32)(33)(34). The mechanisms of these apoE4-mediated detrimental effects are largely unknown.…”
mentioning
confidence: 99%